Sustainable oil palm cultivation through a One Health perspective: Linking biodiversity, ecosystem functioning and public health - Alain Rival; Marc Ancrenaz; Philippe Guizol; Isabelle Lackman; Sempe Burhan; Denis Fabre; Muhammad Firdaus Sulaiman; Marcel Djama; François Roger (Agricultural Systems, 2026)

“Engaging the Enemy”: Orangutan (Pongo pygmaeus morio) Conservation in Human Modified Environments in the Kinabatangan floodplain of Sabah, Malaysian Borneo - Felicity Oram; Mohamed Daisah Kapar; Abdul Rajak Saharon; Hamisah Elahan; Pravind Segaran; Shernytta Poloi; Haslan Saidal; Ahbam Abulani; Isabelle Lackman; Marc Ancrenaz (International Journal of Primatology, 2022)
Throughout the equatorial tropics, forest conversion to agriculture often fragments crucial primate habitat. In 30 years, 80% of the alluvial lowland forests along the Kinabatangan River in Sabah, Malaysian Borneo, have been supplanted by oil palm ( Elaeis guineensis ) plantations. Today, only about 20% of the former orangutan ( Pongo pygmaeus morio ) population remains in the region. Because most of the land is now under the tenure of agribusiness companies, we used a pragmatic approach of mixed biosocial methods and citizen science engagement of oil palm growers (N = 6) as active conservation partners to study orangutan use of the privately administered landscape between protected forest fragments. We found that 22 of 25 remanent forest patches (0.5 to 242 hectares) surveyed within plantations contained food or shelter resources useful for orangutans. Of these, 20 are in regular transitory use by wider-ranging adult male orangutans, and in 9 patches, females are resident and raising offspring isolated within oil palm plantations. These findings indicate that orangutans retain a measure of normal metapopulation dynamics necessary for viability at the landscape level despite drastic habitat modification. We found that barriers to in situ conservation in these agroforest matrices were due to the following misconceptions across sectors: 1) Good farming practices require exclusion of wildlife; 2) Orangutans seen in plantations must be “rescued” by people; and 3) Translocation is an appropriate conservation strategy, and nondetrimental to orangutans. Our exploratory study exemplifies the value of biosocial methods and collaboration with industrial-scale farmers to support primate resilience in forests fragmented by agriculture.

Effects of Karst Forest Degradation on Pulmonate and Prosobranch Land Snail Communities in Sabah, Malaysian Borneo - MENNO SCHILTHUIZEN; THOR‐SENG LIEW; BERJAYA BIN ELAHAN; ISABELLE LACKMAN‐ANCRENAZ (Conservation Biology, 2005)
Limestone (karst) outcrops in Southeast Asia are rich in land snails. Certain groups of land snails, in particular Prosobranchia species, are restricted to limestone and show a high degree of short‐range endemism. Karst habitats are, however, seriously degraded by quarrying, logging, agriculture, and burning. The effect of these disturbances on land snail fauna is unknown, so we studied paired primary and secondary forest localities on six separate limestone hills in Sabah, Malaysian Borneo. Land snails were sampled with a standard protocol and identified to species level. More than 16,000 individuals, belonging to 74 species, were recorded. In most sites, snail diversities did not differ between disturbed and undisturbed plots. However, pulmonate snails were significantly more abundant at disturbed localities than prosobranch snails, whereas abundances for both groups were similar at undisturbed sites. Because Prosobranchia contain many site‐endemic species, our findings suggest that continued exposure to these disturbances will eventually lead to extinctions in this group.

Orangutan Nesting Behavior in Disturbed Forest of Sabah, Malaysia: Implications for Nest Census - Marc Ancrenaz; Romain Calaque; Isabelle Lackman-Ancrenaz (International Journal of Primatology, 2004)